Serviço social : influências religiosas, constituição da profissão e os desafios atuais - Fehlberg, Maria da Penha Almeida (2009)
The goal of this work is to know the religious influence at the Social Work, and understand the beginning of the profession, the woman s function and its challenges knowdays. The objective is to collaborate at the knowledge construction of Social Work s area, as well deepen the studies on theological area, considering that we all live in a globalized word, neoliberal, where the change on the demands for the construction are constants. This way, it looks for a rereading of many authors to hit teh objective, actually doing a re on his rights. The Social Work is here analyzed considering the religious influence in its surges beyond the Catholic Church s convocation to the charities ladies, to the developing of the catholic social action, the practice of helping, the charity exercise and the solidarity. The protestant influence and the Thomism philosophy in his origin, also highlights. Therefore, nowadays, the Social Work is a profession that works the social questions, looking for the citizenship effect and the guaranties to citizen s rights. The relation with religion has been being denied, presenting the Social Work surging with the worsening of social question coming from capitalism. That is why in its developing like socially legitimized profession and its political ethical project carries it to the hurricane s eye on the fight to the social rights.